2021
DOI: 10.1002/mds.28865
|View full text |Cite
|
Sign up to set email alerts
|

TMEM151A Variants Cause Paroxysmal Kinesigenic Dyskinesia: A Large‐Sample Study

Abstract: Background Paroxysmal kinesigenic dyskinesia (PKD) is the most common type of paroxysmal dyskinesias. Only one‐third of PKD patients are attributed to proline‐rich transmembrane protein 2 (PRRT2) mutations. Objective We aimed to explore the potential causative gene for PKD. Methods A cohort of 196 PRRT2‐negative PKD probands were enrolled for whole‐exome sequencing (WES). Gene Ranking, Identification and Prediction Tool, a method of case–control analysis, was applied to identify the candidate genes. Another 32… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
28
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 29 publications
3
28
2
Order By: Relevance
“…7 No other de novo class IV or V variant was identified in this cohort. The TMEM151A mutation was identified in one of 23 patients of our PRRT2negative PKD cohort, which is in accordance with the frequency of 4.8% found by Tian et al 1 We report on a de novo mutation in TMEM151A in a patient with PKD. Our findings confirm TMEM151A variants as a genetic cause of PKD and suggest that de novo mutations in this gene are infrequently responsible for ---------------------------------------------------------------------------------------------------------------------- sporadic PKD cases.…”
Section: De Novo Mutation In Tmem151asupporting
confidence: 92%
See 2 more Smart Citations
“…7 No other de novo class IV or V variant was identified in this cohort. The TMEM151A mutation was identified in one of 23 patients of our PRRT2negative PKD cohort, which is in accordance with the frequency of 4.8% found by Tian et al 1 We report on a de novo mutation in TMEM151A in a patient with PKD. Our findings confirm TMEM151A variants as a genetic cause of PKD and suggest that de novo mutations in this gene are infrequently responsible for ---------------------------------------------------------------------------------------------------------------------- sporadic PKD cases.…”
Section: De Novo Mutation In Tmem151asupporting
confidence: 92%
“…We read with great interest the article by Tian and colleagues. 1 Heterozygous mutations in TMEM151A, encoding transmembrane protein 151 A, a protein of undetermined function, have been very recently associated with paroxysmal kinesigenic dyskinesia (PKD) in the Chinese population. [1][2][3][4] TMEM151A is highly expressed in the brain, including the cerebral cortex and the thalamus and is highly conserved among species.…”
Section: De Novo Mutation In Tmem151amentioning
confidence: 99%
See 1 more Smart Citation
“…To date, TMEM151A mutations have been reported in 52 PKD patients (including our cohort). 4,5 No obvious genotype-phenotype correlation was observed. Interestingly, all studies showed a high frequency of mutations in sporadic cases.…”
mentioning
confidence: 94%
“…3 The lack of known inheritance could be partially attributable to the incomplete penetrance, which has been observed in TMEM151A variants very recently. 4,5 These complex genetic conditions limit the utility of traditional genetic segregation analysis. To date, the roles of genes operating via dominant transmission in PRRT2negative PKD patients have not been systematically studied.…”
mentioning
confidence: 99%